SAT0417 Insight into the Role of Meniscal Extrusion and Bone Marrow Lesions in Knee Osteoarthritis Progression and their Impact on Response to Strontium Ranelate Treatment in A Subset of Patients from the SEKOIA Study. (10th June 2014) - Roubille, C.; Martel-Pelletier, J.; Abram, F.; Dorais, M.; Delorme, P.; Raynauld, J.-P.; Pelletier, J.-P.
Abstract : Background: Knee osteoarthritis (OA) structural changes are complex and comprise cartilage volume loss as well as meniscal lesions, which were shown to promote cartilage loss. Recently, strontium ranelate (SrRan) was demonstrated to have DMOAD properties (1, 2) . Objectives: We thus further evaluated the role of meniscal extrusion (mExt) on knee OA progression and its impact on response to SrRan treatment assessed by X-rays (change in joint space width [JSW]) and qMRI (cartilage volume loss [CVL] in the medial compartment) at 36 months (M36) in subjects with (mExt+) or without (mExt) meniscal extrusion, in association (+) or not (-) with bone marrow lesions (BML). Methods: Patients from the qMRI substudy of the S rRan E fficacy in K nee O steoarthrI tis triA l (SEKOIA) (modified intention-to-treat, n=330) were stratified based on whether mExt (mExt+, n=60; mExt-, n=270) and BML were present or not (BML+, n=84; BML-, n=246) and on their association in the medial compartment at baseline. CVL was assessed by qMRI and JSW by X-rays at baseline and M36. Results: In the placebo group, mExt+ patients demonstrated significantly more JSW loss (-0.76±0.67 mm; p=0.002) and CVL in the medial compartment (-10.40±4.23%; p=0.0005) than mExt- patients (-0.35±0.61 mm and -7.60±4.63%, respectively). mExt-/BML+ patients (n=18) had significantly more JSW loss (-0.77±0.68 mm; p=0.003) and a trend (-9.57±5.29%; p=0.090) toward more CVL compared to mExt-/BML- patients (n=68) (-0.23±0.55 mm and -7.08±4.33%, respectively). mExt+/BML+ patients (n=12) had a trend toward more CVL in the medial compartment (-11.22±1.90%; p=0.103) than mExt+/BML- (n=14) (-9.69±5.50%), while JSW change showed no difference. Importantly, the JSW loss and CVL in the medial compartment were greater when mExt and BML were both present simultaneously in this compartment. In mExt+ patients, while no difference was found in the JSW loss between groups, SrRan at 2 g/day reduced the CVL in the plateaus (-5.74±3.54%; p=0.007) and a trend toward a decrease in the medial plateaus (-4.90±5.19%; p=0.081) compared to the placebo (-10.01±5.79% and -9.07±8.74% respectively). In the mExt+/BML+ patients, SrRan 2 g/day significantly reduced the CVL in the medial plateaus (-1.13±2.24% vs -11.45±4.47% for the placebo; p=0.046), whereas there was no difference for the JSW loss. Conclusions: The progression of knee OA assessed both by X-rays and qMRI was greater in mExt+ patients, and was further increased when co-localized with BML. Based on qMRI, SrRan 2 g/day showed beneficial DMOAD structural effects in mExt+ and mExt+/BML+ patients, targeting a subpopulation at higher risk of knee OA progression, while JSW loss was not sensitive enough to provide evidence of such effects. References: Reginster JY. et al. Ann Rheum Dis 2013;72:179-86. Pelletier JP et al. Ann Rheum Dis. 2013 Dec 2. doi: 10.1136/annrheumdis-2013-203989. Disclosure of Interest: C. Roubille: None declared, J. Martel-Pelletier Shareholder of: ArthroLab Inc., F. Abram Employee of: ArthroLab Inc., M. Dorais Consultant for: ArthroLab Inc., P. Delorme: None declared, J.-P. Raynauld Consultant for: ArthroLab Inc., J.-P. Pelletier Shareholder of: ArthroLab Inc. DOI: 10.1136/annrheumdis-2014-eular.2539